مستويات MASP-2 المصليّة عند أطفال سوريين مصابين بابيضاض الدم اللمفاوي الحاد - الصالح جمانة; حرب راغب (Latakia University Journal -Medical Sciences Series, 2016)
خلافاً للمناعة التلاؤمية ومكونات معينة من المناعة الخلقية، قليل ما هو معلوم عن وظيفة جملة المتممة في تعزيز وكبت السرطان. يُعتبر سبيل الليكتين لتفعيل المتممة جزءاً هاماً من المناعة الخلقية. إنه مكتنف بشكل رئيسي في طهاية وانحلال الممراضات وتوظيف الخلايا الالتهابية. تهدف دراستنا إلى تقييم العلاقة بين المستويات المصلية لبروتياز السيرين المشارك لليكتين الرابط للمانوز -2 (MASP-2) قبل وبعد المعالجة الكيميائية عند أطفال سوريين مصابين بابيضاض الدم اللمفاوي الحاد (ALL) acute lymphoblastic leukemia بهدف إيجاد علاقة تساعد في التنبؤ المبكر لاستجابة المرضى للمعالجة الكيميائية، حيث تمت الدراسة بين عامي 2013 و 2014 في مستشفى الأطفال الجامعي بدمشق وشملت 37 طفلاً مشاركاً مصاباً بابيضاض الدم اللمفاوي الحاد، حيث تم قياس مستويات بروتياز السيرين المشارك لليكتين الرابط للمانوز-2 (MASP-2) المصلية بطريقة الممتز المناعي المرتبط بالإنزيم (ELISA). فكانت النتيجة أن وُجِدَ أن مستويات MASP-2 المصليّة قد انخفضت بشكل ملحوظ بعد المعالجة الكيميائية عند الأطفال المصابين بابيضاض الدم اللمفاوي الحاد، وكذلك وُجِدَ علاقة ارتباط قوية بين مستويات الواسم قبل وبعد المعالجة. In contrast to adaptive immunity and to certain components of innate immunity, only little is known on the influence of the complement system on cancer suppression and promotion . The lectin pathway of complement activation is an important part of innate immunity. It is mainly involved in opsonisation and lysis of pathogens and in recruitment of inflammatory cells. Our study aimed to assess the relationship between MASP-2 serum levels before and after chemotherapy in Syrian children with acute lymphoblastic leukemia, aiming to find a relation, which serve in early forecast of patients response to chemotherapy, where the study has been done at Children University Hospital in damascus between 2013-2014. This study included 37 children diagnosed with acute lymphoblastic leukemia (ALL). The levels of Mannose-Binding Lectin-associated Serine Protease-2 (MASP-2) were determined by Enzyme Linked Immuno Sorbent Assay (ELISA). The result was that serum levels of MASP-2 was strongly reduced after chemotherapy in children with acute lymphoblastic leukemia, and a strong correlation between serum marker levels before and after chemotherapy was found.